A comprehensive review of clear cell stromal tumor of the lung: integrating clinicopathology and molecular pathogenesis - Luo, Liping; Lv, Liang; Zeng, Ying (Frontiers in Oncology, 2026)
Clear cell stromal tumor (CCST) is a newly recognized mesenchymal neoplasm of the lung, with a recurrent YAP1::TFE3 gene fusion in most cases and characterized histologically by spindle, epithelioid cells, with variably clear to pale eosinophilic cytoplasm and prominent vascularity. Due to its rarity and the absence of specific immunohistochemical markers beyond TFE3, diagnosis remains challenging. Currently, only thirty cases have been documented. This narrative literature review synthesizes current advances to enhance understanding of this entity.